Prevalence and associated risk factors of clostridium difficile infection in type 2 diabetes mellitus patients treated with antibiotics - Rahman, Rozanah Abd (2010)
Clostridium difficile infection (COl) is one of the most common nosocomial infection and it is one of the leading cause for antibiotic associated diarrhea. COl is currently on the rise and it is associated with high morbidity and mortality among in hospital patients. Some authors consider diabetes mellitus as a risk factor for COl and stools from diabetic patients have revealed a higher concentration of Clostridium difficile toxin compared to healthy individual. This study was a cross-sectional study and was performed from August 2009 until May 2010 in Hospital University Science Malaysia (HUSM). All adults aged 30 years and above with documented history of type 2 diabetes mellitus who were admitted to general medical wards and received antibiotics, willing to participate and consented were enrolled in this study. A total of 159 patients were involved in this study. Stool specimens were collected and tested for presence of toxin and few blood investigations were taken. Demographic data together with laboratory results were collected and recorded in a standard data collection sheet. Variables were analyzed and chi square test and logistic regression test were used to identify significant association with CDI. Among 159 patients enrolled in this study, 14 of 159 (8.8%) were tested positive for the presence of C. difficile toxins. The mean age of the patients involved was 60.47 ±10.98. Those in the positive C. difficile group has a mean age of 53.79 ±14.19 and those in the negative C. difficile group has a mean age of 61.11 ±10.46. We found that none of the laboratory markers were significantly associated with COl. These included total white count, albumin, urea, creatinine and HbA1c. From univariate analysis, bacteremia was associated with COl (p=0.043) and among the symptoms, diarrhea and abdominal pain were associated with COl with p=0.002 and p=0.001 respectively. From multivariate analysis we identified that imipenem (p=0.006, OR; 30.1), cefoperazone (p=0.036, OR; 9.5) and proton pump inhibitor (p=0.041, OR; 13.7) were strongly associated with CDI. The prevalence of Clostridium difficile infection in patients with type 2 diabetes mellitus who were treated with antibiotics was 8.8% and among the antibiotics strongly associated with COl were imipenem and cefoperazone. Proton pump inhibitor was also strongly associated with COl and presence of bacteremia was also associated with COl. These findings will allow clinician to identify patients with high risks of developing COl.